2018
DOI: 10.1152/ajpendo.00010.2017
|View full text |Cite
|
Sign up to set email alerts
|

Using [2H]water to quantify the contribution of de novo palmitate synthesis in plasma: enabling back-to-back studies

Abstract: An increased contribution of de novo lipogenesis (DNL) may play a role in cases of dyslipidemia and adipose accretion; this suggests that inhibition of fatty acid synthesis may affect clinical phenotypes. Since it is not clear whether modulation of one step in the lipogenic pathway is more important than another, the use of tracer methods can provide a deeper level of insight regarding the control of metabolic activity. Although [H]water is generally considered a reliable tracer for quantifying DNL in vivo (it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…After exchange, 2H-enriched acetone is extracted with chloroform and assayed by gas chromatography–mass spectrometry. 37 Hepatic palmitate and glyceride enrichments and content were assessed in saponified extracts spiked with internal standards (1,1,2,3,3- 2 H 2 ]Glycerol and Heptadecanoic acid) 32 , 38 . Glucose fluxes were assessed using non–steady-state equations (volume of distribution of glucose= 130 ml/kg).…”
Section: Discussionmentioning
confidence: 99%
“…After exchange, 2H-enriched acetone is extracted with chloroform and assayed by gas chromatography–mass spectrometry. 37 Hepatic palmitate and glyceride enrichments and content were assessed in saponified extracts spiked with internal standards (1,1,2,3,3- 2 H 2 ]Glycerol and Heptadecanoic acid) 32 , 38 . Glucose fluxes were assessed using non–steady-state equations (volume of distribution of glucose= 130 ml/kg).…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to examine whether other metabolic parameters are able to differentiate the physical activity level. The methods used in the present study make it possible to explore the utilization of multiple energy substrates such as fatty acid oxidation and glycogen storage in the liver and muscle [6], whereas others also measured fatty acid and lipid synthesis using D 2 O [37,38]. In addition, protein breakdown analysis of the different tissues would provide a more complete metabolic picture in regards to the physical activity level.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies on the effects of low concentrations of deuterium on rats and mice show that the organism accelerates its metabolism [ 43 , 52 , 53 , 54 ]. In this regard showed that one could use ddw water to test inhibitors of de novo lipogenesis (DNL) by performing back-to-back studies in higher species, treat nonhuman primates with platensimycin, an inhibitor of fatty acid synthase [ 55 ]. Broad varieties of morphological and physiological changes were observed in deuterium-treated cells and organisms, including changes in fundamental processes such as cell division or energy metabolism [ 56 ].…”
Section: Resultsmentioning
confidence: 99%